Mitigasi Bencana Banjir Melalui Metode Simulasi Pada Siswa/i di SD Islam Arraisiyah - Yanti Yanti; Ati Kusumawati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Disasters can occur anywhere and anytime that can disrupt various aspects of a person's life, children are one of the groups of people who are vulnerable to natural disasters. This vulnerability is caused by the limited understanding of the dangers of disaster risks in their surrounding environment. So involving children in disaster mitigation efforts is one of the efforts to strengthen children's resilience in facing disasters in the future. This study uses a descriptive qualitative method with a classroom action research approach implemented at SD Islam Arraisiyah. The subjects were 18 students in grade 5 (five). The implementation of the simulation method in flood disaster mitigation efforts for students starts from the planning stage, implementation stage, observation stage, and reflection stage. There was an increase in student understanding after the socialization and preparedness training using the simulation method, as seen from the number of students who answered correctly in the post-test the efforts they could make to save themselves, namely 15 students answered correctly about flood prevention efforts, 12 students answered correctly about the efforts they could make when a flood disaster occurs, and 17 students answered correctly about the efforts they could make after a disaster occurs.